Pension Systems in Europe. Case of Portugal - Jarosław Poteraj (Contemporary Economics)
The article presents an insight into the old age pension system in Portugal. The author’s goal was to present both past and present solutions employed by the Portuguese’s pension system, in search for ideas worth consideration in international comparisons. In the summary, the author highlights as a particular Portuguese approach, on the background of other countries, the fact of using in Portugal definite part of VAT income for pension system financing.